Bento Rodrigues: paisagem cultural minerária - Anielle Kelly Vilela Freitas (2018)
The region comprised by the settlement of Bento Rodrigues and its adjacent territory, located in Minas Gerais, Brazil, was internationally recognized due to the disaster that occurred on November 5, 2015, when the dam ofFundão mineral tailings was broken, releasing more than 30 million of m³ of mud in the Rio Doce Basin, causing one of the biggest socio-environmental disasters in Brazil. This work seeks to analyze this region from the concepts of cultural landscape and industrial patrimony, key concepts within the area of cultural heritage, which seek to analyze the interactions of man and nature over the territory, and the preservation and conservation of goods from industrialization, respectively. Moreover, it was used for the analysis, the issue of cultural significance and analysis based on values, which further expand the discussion, trying to make it less techno-scientific, trying to broaden participation in the processes to other actors involved with the goods and landscapes studied. In order to find examples to guide this analysis, a survey of industrial properties and landscapes recognized internationally and nationally was carried out, aiming to understand the objectives and methodologies used for their recognition and valuation, for then decide the procedures to be used in this work. From this, the analysis and characterization of the area of the Bento Rodrigues Cultural Landscape was carried out based on a process derive on the analysis of the British landscape and the methodologies of access to values and meanings developed by the Getty Conservation Institute, demonstrating the applicability of this method to the Brazilian situation, which is in accordance with the concepts defended by this study.